The influence of gratitude on pre-service teachers’ career goal self-efficacy: Chained intermediary analysis of meaning in life and career calling - Zhang, Sensen; Tang, Yulun; Yong, Shaohong (Frontiers in Psychology, 2022)
Objective: To explore the relationship between gratitude, meaning in life (MIL), career calling, and career goal self-efficacy (CGSE) of the pre-service teachers in the Free Teacher Education program in China and the internal mechanism of action. Methods: Used gratitude, MIL, career calling, and CGSE questionnaires to investigate 801 pre-service teachers; IBM SPSS 25.0 and AMOS 24.0 were used for data processing, and SPSS macro program Model 6 for the mediating mechanism. Results: (1) Gratitude was positively correlated with MIL and career calling. MIL was positively correlated with career calling. Gratitude, MIL, and career calling were significantly and positively associated with CGSE. (2) Gratitude influences pre-service teachers’ CGSE mainly through the independent intermediary of MIL and career calling, and the chain intermediary of MIL→ career calling, three indirect effects. Conclusion: Gratitude not only predicts CGSE of pre-service teachers through the independent intermediary of MIL and career calling indirectly, but also through the chain intermediary of MIL and career calling indirectly.